2017
DOI: 10.1016/j.ymeth.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Genome organization in the nucleus: From dynamic measurements to a functional model

Abstract: A biological system is by definition a dynamic environment encompassing kinetic processes that occur at different length scales and time ranges. To explore this type of system, spatial information needs to be acquired at different time scales. This means overcoming significant hurdles, including the need for stable and precise labeling of the required probes and the use of state of the art optical methods. However, to interpret the acquired data, biophysical models that can account for these biological mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
2
15
0
1
Order By: Relevance
“…We monitor the dynamics of different genomic sites in the nucleus, and by thoroughly analyzing the dynamics, we can extract relevant information about the structure, organization, and function. 63 More specifically, we mainly use two methods. In the first, we label telomeres, centromeres, or any genetic site in live cells and follow their motion in time by single-particle tracking (SPT).…”
Section: Tad Related Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…We monitor the dynamics of different genomic sites in the nucleus, and by thoroughly analyzing the dynamics, we can extract relevant information about the structure, organization, and function. 63 More specifically, we mainly use two methods. In the first, we label telomeres, centromeres, or any genetic site in live cells and follow their motion in time by single-particle tracking (SPT).…”
Section: Tad Related Proteinsmentioning
confidence: 99%
“…During the last few years, we developed a methodology for studying the organization of the genome in the nucleus by using live cell imaging. We monitor the dynamics of different genomic sites in the nucleus, and by thoroughly analyzing the dynamics, we can extract relevant information about the structure, organization, and function . More specifically, we mainly use two methods.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the recurrent detection of irregular 10-nm fibers by cryo-TEM of thin nuclear sections is questioning the relevance of solenoid or helicoid models of nucleosome arrays (6)(7)(8). This problem has not been clarified by probing the motion of chromosomes in vivo, although dynamic measurements offer a unique opportunity to infer structural properties of genome organization (9). Indeed, we and others have shown that chromosome dynamics in yeast is characterized by sub-diffusive behavior detected by a non-linear temporal variation of the mean square displacement (MSD) of chromosome loci (10)(11)(12)(13)(14)(15)(16):…”
mentioning
confidence: 99%
“…The interaction of chromatin proteins with their substrate is dynamic, even for the architectural proteins that forms "stable" loops, such as CTCF and cohesin [24]. It takes energy both for chromatin proteins to interact with their substrate, as well as to preserve form.…”
Section: Figurementioning
confidence: 99%